Map showing route of sledge party during spring 1907 / Ejnar Mikkelsen - Mikkelsen, Ejnar, 1880-1971 (1907)
Shows course, date and location of camps where observations of water depth and wind speed were made. Red ink shows course and camps according to dead reckoning.; Signed by Mikkelsen.; Indexed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography Grayscale; 1:1,000,000